1995
DOI: 10.1111/j.1365-2923.1995.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

The feminization of the medical profession in Israel

Abstract: Two factors have caused major changes in the gender composition of the Israeli medical profession in recent years: (i) a wave of immigration from the former USSR, which increased the doctor population by approximately 70% and which included a majority of women physicians, and (ii) the entry of more Israeli women into medical school. This report presents the current gender status of the Israeli medical profession, regarding students and physicians, and the choice of medical specialty and academic seniority, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
1
7
0
4
Order By: Relevance
“…The majority of applicants were women, which is in line with multiple reports on so-called feminization of medicine (Notzer & Brown 1995;Paik 2000;Thomas 2000).…”
Section: Discussionsupporting
confidence: 81%
“…The majority of applicants were women, which is in line with multiple reports on so-called feminization of medicine (Notzer & Brown 1995;Paik 2000;Thomas 2000).…”
Section: Discussionsupporting
confidence: 81%
“…Reports from western industrialized countries have shown an increase in the percentage of women entering medical school (e.g. references 17–19), and in some countries women entrants outnumber men; 17 , 20 –22 The large proportion of women applying to and being accepted by medical schools provides evidence of equal access 23 . The most recent data from the Association of American Medical Colleges (AAMC) 24 reveals that the proportion of women applicants to US medical schools has plateaued; 44% of new entrants in the 1998–99 academic year were women.…”
Section: Current State Of Affairsmentioning
confidence: 99%
“…The lower success rates of women in scaling the academic ladder are similar to other reports the majority of respondents preferred mail as the method of communication. As Internet use continues to grow at a record of women physicians and women scientists (6,(19)(20)(21)(22)(23). A cohort study of medical school graduates showed that women pursue pace (25), it will be important to determine whether electronic communication is embraced by more members over time.…”
Section: Work Settingmentioning
confidence: 99%